Are there bubbles in the Sterling-dollar exchange rate? New evidence from sequential ADF tests - Timo Bettendorf; Wenjuan Chen (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2013)
There has been mixed evidence regarding the existence of rational bubbles in the foreign exchange markets. This paper introduces recently developed sequential unit root tests into the analysis of exchange rates bubbles. We nd strong evidence of explosive behavior in the nominal Sterling-dollar exchange rate. However, this explosive behavior should not be simply interpreted as evidence of rational bubbles, as we show that it might be driven by the relative prices of traded goods.
Keywords: C1; F3; 330; exchange rates; rational bubbles; sequential unit root test